SUNny Ways: The Role of the SUN-Domain Protein Mps3 Bridging Yeast Nuclear Organization and Lipid Homeostasis - Sosa Ponce, Maria Laura; Moradi-Fard, Sarah; Zaremberg, Vanina; Cobb, Jennifer A. (Frontiers in Genetics, 2020)
Mps3 is a SUN (Sad1-UNC-84) domain-containing protein that is located in the inner nuclear membrane (INM). Genetic screens with multiple Mps3 mutants have suggested that distinct regions of Mps3 function in relative isolation and underscore the broad involvement of Mps3 in multiple pathways including mitotic spindle formation, telomere maintenance, and lipid metabolism. These pathways have largely been characterized in isolation, without a holistic consideration for how key regulatory events within one pathway might impinge on other aspects of biology at the nuclear membrane. Mps3 is uniquely positioned to function in these multiple pathways as its N- terminus is in the nucleoplasm, where it is important for telomere anchoring at the nuclear periphery, and its C-terminus is in the lumen, where it has links with lipid metabolic processes. Emerging work suggests that the role of Mps3 in nuclear organization and lipid homeostasis are not independent, but more connected. For example, a failure in regulating Mps3 levels through the cell cycle leads to nuclear morphological abnormalities and loss of viability, suggesting a link between the N-terminal domain of Mps3 and nuclear envelope homeostasis. We will highlight work suggesting that Mps3 is pivotal factor in communicating events between the nucleus and the lipid bilayer.